2007
DOI: 10.1002/cjoc.200790272
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of the Self‐assembled Monolayers of 1‐Adamantanethiolate and Its Derivatives on Au(111) Surfaces

Abstract: The self-assembled monolayers (SAMs) of 1-adamantanethiolate and its derivatives on Au(111) surface were investigated. Density functional theory (DFT) calculation indicates that the most stable configuration for absorption is at the face centered cubic (fcc)-bridge site. Canonical ensemble molecular dynamics (MD) simulations were carried out to study the structures and energies of the SAMs. The ordered structures of the SAMs were analyzed by means of radial distribution function and the relative stability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…We will explore this in more detail in section 3.4. For C12, our calculated tilt angle is in agreement with some simulation and experimental studies which found the tilt angle to be in the range of 24 ± 4°. ,, Although for C12 our calculated tilt angle is lower than 33.7°, which is reported by Fenter et al, for n ≥ 16, our results show excellent agreement with their experimental results (see Figure ). It is interesting to see a similar transitional regime at n = 15, in apparent agreement with “short” and “long” chain regimes reported in experiments by Fenter et al…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We will explore this in more detail in section 3.4. For C12, our calculated tilt angle is in agreement with some simulation and experimental studies which found the tilt angle to be in the range of 24 ± 4°. ,, Although for C12 our calculated tilt angle is lower than 33.7°, which is reported by Fenter et al, for n ≥ 16, our results show excellent agreement with their experimental results (see Figure ). It is interesting to see a similar transitional regime at n = 15, in apparent agreement with “short” and “long” chain regimes reported in experiments by Fenter et al…”
Section: Resultssupporting
confidence: 91%
“…Self-assembled monolayers (SAMs) can be grown from solutions, gas and vapor deposition. They form covalent bonds with various types of metallic substrates such as Au, Ag, Cu, Pt, Pd, Hg, and Si .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the original work of Hautman and Klein, molecular simulation methods have been widely used, as an alternative tool, to study SAMs at the molecular level and to investigate their frictional properties. One of the purposes of molecular level simulations of a lubricant is to study the origin of friction at atomic level and to find possible methods for reducing friction coefficient. During sliding, stick–slip dynamics for alkanethiols on gold have been observed with AFM experiments and in simulations. ,, This stick–slip behavior was suggested to be a function of geometric structure of substrate as well as discontinuous movement of monolayers. Structural origin of this stick–slip behavior is not understood well.…”
Section: Introductionmentioning
confidence: 99%
“…SAMs with different chain lengths form ordered structures where backbones of the molecules are tilted in a certain direction. 1,[8][9][10][11][12][13][14] Subtle variation in SAMs structural characteristics results in significant changes in their adhesion, friction, and other properties which are crucial for their efficient utilization in technological applications. Various factors such as type of substrate and contact, chain length, and packing density may affect structural characteristics of the SAM systems.…”
Section: Introductionmentioning
confidence: 99%